Gender-related aspects in occupational allergies – Secondary publication and update - Raulf, Monika (World Allergy Organ J, 2017)
For years occupational allergies have been among the most frequently recorded occupational diseases, and both the skin as well as the respiratory tract may be affected. An estimated 9 to 15% of adult asthma is (partially) caused by work-related exposure. Gender-specific differences in exposure cause different risks in the workplace which affect the health of employees. This also applies to exposure and working conditions when handling sensitizing working substances. The presented gender-specific analysis of the German documentation of confirmed occupational respiratory allergic diseases and occupational skin diseases reveals clear differences between men and women in the number of diseases and also in exposure conditions and working areas.